Vertebrobasilar Junction Angle Over 90°: A Potential Imaging Marker Associated With Vertebrobasilar Atherosclerosis - Li, Jia; Yang, Wen-Jie; Zheng, Lu; Du, Heng; Chu, Winnie Chiu-Wing; Leung, Thomas Wai-Hong; Chen, Xiang-Yan (Frontiers in Neuroscience, 2022)
Objective: Whether the cerebral vascular variations play an important role in the progression of intracranial atherosclerosis is yet largely unclear. We aimed to investigate the relationship between the magnitude of the vertebrobasilar junction (VBJ) angle and the imaging features of vertebrobasilar artery atherosclerosis. Methods: Adult patients with acute ischemic stroke or transient ischemic attack undergoing a 3.0-tesla vessel wall magnetic resonance imaging (VW-MRI) scanning were consecutively included. Imaging features of vertebrobasilar artery atherosclerosis were assessed on the reconstructed short axis of VW-MRI at the most stenotic site. The VBJ angle degree was measured on magnetic resonance angiography and classified into the angle ≥90° or <90°. Results: Among 68 patients (mean age = 63.5 ± 9.4 years old; 63.2% were male) with vertebrobasilar atherosclerosis, 33 had a VBJ angle ≥90° and 35 had a VBJ angle <90°. Compared to the vertebrobasilar plaques with VBJ angle <90°, those with VBJ angle ≥90° had a heavier plaque burden (84.35 vs. 70.58%, p < 0.001) and higher prevalence of intraplaque hemorrhage (17.1 vs. 3.3%, p = 0.01). In the regression analyses, the VBJ angle ≥90° was also robustly associated with plaque burden (odds ratio, 1.11; 95% confidential interval, 1.043–1.18; p = 0.001) and intraplaque hemorrhage (odds ratio, 5.776; 95% confidential interval, 1.095–30.46; p = 0.039) of vertebrobasilar atherosclerosis. Conclusion: The VBJ angle over 90° might aggravate the vessel wall condition of the atherosclerotic vertebrobasilar arteries, which might serve as a potential risk factor for vertebrobasilar atherosclerosis.